When the ribosomal DNA does not tell the truth: The case of the taxonomic position of Kurtia argillacea, an ericoid mycorrhizal fungus residing among Hymenochaetales - Kolařík, Miroslav; Vohník, Martin (Fungal biology, 2018)
The nuclear ribosomal DNA (nuc-rDNA) is widely used for the identification and phylogenetic reconstruction of Agaricomycetes. However, nuc-rDNA-based phylogenies may sometimes be in conflict with phylogenetic relationships derived from protein coding genes. In this study, the taxonomic position of the basidiomycetous mycobiont that forms the recently discovered sheathed ericoid mycorrhiza was investigated, because its nuc-rDNA is highly dissimilar to any other available fungal sequences in terms of nucleotide composition and length, and its nuc-rDNA-based phylogeny is inconclusive and significantly disagrees with protein coding sequences and morphological data. In the present work, this mycobiont was identified as Kurtia argillacea (= Hyphoderma argillaceum) residing in the order Hymenochaetales (Basidiomycota). Bioinformatic screening of the Kurtia ribosomal DNA sequence indicates that it represents a gene with a non-standard substitution rate or nucleotide composition heterogeneity rather than a deep paralogue or a pseudogene. Such a phenomenon probably also occurs in other lineages of the Fungi and should be taken into consideration when nuc-rDNA (especially that with unusual nucleotide composition) is used as a sole marker for phylogenetic reconstructions. Kurtia argillacea so far represents the only confirmed non-sebacinoid ericoid mycorrhizal fungus in the Basidiomycota and its intriguing placement among mostly saprobic and parasitic Hymenochaetales begs further investigation of its eco-physiology.
Keywords: zastoupení bazí; Base Composition; GC Rich Sequence; DNA, Mitochondrial; ribozomální DNA; Mycorrhizae; mezerníky ribozomální DNA; elongační faktor 1; DNA, Ribosomal Spacer; Phylogeny; mitochondriální DNA; Basidiomycota; mykorhiza; DNA, Ribosomal; fylogeneze; Peptide Elongation Factor 1; GC bohatá sekvence